Taxonomic revision of the genus Xenogryllus Bolívar, 1890 (Orthoptera, Gryllidae, Eneopterinae, Xenogryllini) - Jaiswara, Ranjana; Dong, Jiajia; Ma, Libin; Yin, Haisheng; Robillard, Tony (Zootaxa, 2019)
Subfamily Eneopterinae has been studied for its diversified acoustic modalities and disjunct distribution. The genus Xenogryllus Bolívar, 1890 is one of the oldest genera of the subfamily, and the first genus of the tribe Xenogryllini. Xenogryllus is known for its low-frequency calling songs and wide distribution across Africa and Asia. It is known from six species and has never been subject to formal taxonomic revision and description of acoustic features of their calling songs is lacking. Therefore, this study consists of a detailed taxonomic revision of all the species. We redescribe or append their taxonomic features using external morphological features and internal genitalic structures. We update the list of Xenogryllus by describing three new spe.